Birth of the Regional Nursing Council of Santa Catarina (1970s) - Maria Lígia dos Reis Bellaguarda; Maria Itayra Padilha; André de Faria Pereira Neto; Miriam Susskind Borenstein (Universidade Federal de Goias, 2015)
The aim of this study was to analyze the circumstances of the creation and establishment of the Regional Nursing Council in the state of Santa Catarina. The research was qualitative and socio-historical, and used content analysis for data treatment. This resulted in two categories: the movement for the creation of the Regional Nursing Council of Santa Catarina and the circumstances surrounding the creation and establishment of the Regional Council of Santa Catarina in 1975. The creation of the Professional Nursing Council arose from the socio-historical and political transformations of health care work in Brazil. The leadership of the Brazilian Nursing Association ensured a certain professional autonomy and power over its work, even when confronted with the fragile understanding of the aims of an agency that supervised its members' nursing work. The study enabled the understanding of the nexuses of influence on the council of nursing, which institutionalized the profession with a registry of nurses, and which also regulated and disciplined the profession.